Insights into the physiology of C-peptide - Vejrazkova, D; Vankova, M; Lukasova, P; Vcelak, J; Bendlova, B (Physiological research, 2020)
Current knowledge suggests a complex role of C-peptide in human physiology, but its mechanism of action is only partially understood. The effects of C-peptide appear to be variable depending on the target tissue, physiological environment, its combination with other bioactive molecules such as insulin, or depending on its concentration. It is apparent that C-peptide has therapeutic potential for the treatment of vascular and nervous damage caused by type 1 or late type 2 diabetes mellitus. The question remains whether the effect is mediated by the receptor, the existence of which is still uncertain, or whether an alternative non-receptor-mediated mechanism is responsible. The Institute of Endocrinology in Prague has been paying much attention to the issue of C-peptide and its metabolic effect since the 1980s. The RIA methodology of human C-peptide determination was introduced here and transferred to commercial production. By long-term monitoring of C-peptide oGTT-derived indices, the Institute has contributed to elucidating the pathophysiology of glucose tolerance disorders. This review summarizes the current knowledge of C-peptide physiology and highlights the contributions of the Institute of Endocrinology to this issue.
Keywords: diabetes mellitus 2. typu; C-peptid; nemoci nervového systému; nemoci cév; Insulin Resistance; Animals; inzulinová rezistence; lidé; Diabetes Mellitus, Type 2; Nervous System Diseases; Humans; Vascular Diseases; zvířata; C-Peptide